2012
DOI: 10.1111/j.1540-5885.2012.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Industrial Design: The “Means” and the “Ends”

Abstract: It is widely accepted that industrial design can play an important role in the development of innovative products, but integrating design‐thinking into new product development (NPD) is a challenge. This is because industrial designers have very different perspectives and goals than the other members of the NPD team, and this can lead to tensions. It has been postulated that the communications between NPD managers and industrial designers are made more difficult because each group uses very different language. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 42 publications
4
71
1
Order By: Relevance
“…Increasingly, evidence suggests that designers frame brand and innovation challenges differently than marketers (Micheli et al 2012;Verganti 2008Verganti , 2011. Indeed, the ability to challenge existing ways of thinking and/or to force organizations to ask Bwhat if^type questions as a means of creating value is consistent with a design thinking approach (Liedtka 2004).…”
Section: The Nature Of Design and Design Thinkingmentioning
confidence: 99%
“…Increasingly, evidence suggests that designers frame brand and innovation challenges differently than marketers (Micheli et al 2012;Verganti 2008Verganti , 2011. Indeed, the ability to challenge existing ways of thinking and/or to force organizations to ask Bwhat if^type questions as a means of creating value is consistent with a design thinking approach (Liedtka 2004).…”
Section: The Nature Of Design and Design Thinkingmentioning
confidence: 99%
“…A high level of interfunctional coordination (IFC) means that functionally specialized groups work towards accomplishing specific NPD tasks and, ultimately, create value for customers (Sarin, 2009). Innovation researchers have identified several barriers to IFC including differences in knowledge and practice (Calantone and Rubera, 2012;Dougherty, 1992;Micheli et al 2012). …”
Section: Npd Success and Interfunctional Coordinationmentioning
confidence: 99%
“…for example, Micheli et al (2012) found that, despite using similar terms and sharing NPD goals, marketers and designers attributed very different meanings to the same words.…”
Section: Sensemaking and Interfunctional Coordinationmentioning
confidence: 99%
“…It is stated that one potential conflict may exist in the collaboration between marketing and design since marketing often relies on a rational, scientific, and profit---based approach, while the designer relies on talent, creative skill, and intuition (Beverland, 2005). Conflicts are also described in terms of being caused by differences in interests, educational background, values and attitudes or by the different use of language (Micheli et al, 2012;Svengren Holm & Johansson, 2005). As a consequence, it is argued, marketers strive towards objectivity, seeking to rely on consumer research into explicit needs and desires, while designers tend to base their creations more on the non---explicit needs of their customers and on studies of their behaviours (Svengren Holm & Johansson, 2005).…”
Section: The Strategic Orientation Of Companies Focusing On Product Dmentioning
confidence: 99%
“…The previous literature on design collaboration (e.g. Micheli, 2012;Svengren Holm, 2005) suggests that the relationship between a creative designer and companies' more commercially---driven functions may easily become tense and problematic, e.g. due to inherent cultural differences.…”
Section: Theoretical Contributionsmentioning
confidence: 99%